PENGARUH GAYA KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KEDISIPLINAN KARYAWAN PADA PT. BANK INDEX SELINDO KC. PLUIT - Ninik Anggraini (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
The purpose of this study was to determine and analyze the influence of leadership style and work environment on employee discipline at PT. Bank Index Selindo KC. whistle. In this study, researchers took a sample location at PT. Bank Index Selindo KC. whistle. The research method used is quantitative method, while quantitative data processing uses statistical analysis. Determination of the sample using the Slovin formula with an error rate of 5% and obtained a sample of 109 people. Data analysis method with validity test, reliability test, classic assumption test, autocorrelation test, regression analysis, t test. f test and coefficient of determination. The results of the analysis are as follows: Leadership style partially has no effect on the discipline of PT. Bank Index Selindo KC. whistle. The results obtained are known for the leadership style variable (X1) has a t count value of -0.051 < t table 1.98260 and has a significance level of 0.549 > 0.05. The work environment partially affects the discipline of PT. Bank Index KC. whistle. From table 4.19 it can be seen that the work environment variable (X2) has a t value of 6.106 > from t table 1.98260 and has a significance of 0.000 <0.05. Leadership style and work environment simultaneously or jointly affect the discipline of employees of PT. Bank Index Selindo KC. whistle. This is indicated by the significance value of 0.000 <0.05, and the calculated F value of 18.656 > from F table 3.08.